Effect of Job Satisfaction on Employee Commitment at PT. Bank Mandiri Regional Credit Card Makassar (Persero) Tbk - Amin, Abd Rahim; Peringga, Bayu; Arimbawa, I Gede Arya Pering; Goeliling, Ardhi; Muhammad, A Fadel (International Humanity Advance, Business & Sciences, 2024)
The purpose of this study was to determine the effect of job satisfaction on employee commitment. This research was conducted at PT Bank Mandiri Regional Credit Card Makassar on a number of employees. Data were collected from 31 respondents using the OCS measurement scale for employee commitment and JDI job satisfaction. The results of the study using regression analysis show that job satisfaction has a positive and significant effect on employee commitment, meaning that the higher the job satisfaction, the higher the work commitment and vice versa.